A new mountain lizard from Montes de León (NW Iberian Peninsula): Iberolacerta monticola astur ssp. nov. (Squamata: Lacertidae) - Arribas, Oscar J.; Galán, Pedro; Remón, Núria; Naveira, Horacio (Zootaxa, 2014)
Iberolacerta populations from the Northern Montes de León (NML) were studied by means of external morphology (scalation and biometry), osteology and genetics (mtDNA and microsatellites), searching for their homogeneity (“intrazonal analysis”) and, once verified, comparing them with Iberolacerta monticola s. str. (from Central Cantabrian Mountains) and I. galani (from Southern Montes de León) (“extrazonal analysis”) from neighboring areas.